Genetic Diversity and Phylogeny of Alocasia Longiloba Miq. Indonesia Accessions based on trnL-F Intergenic Spacer Region - Asih, Ni Putu Sri; Purnomo; Daryono, Budi Setiadi (JST (Jurnal Sains dan Teknologi), 2023)
Alocasia longiloba Miq. is a member of the Araceae family, which was complex and has diverse leaf shapes, color, and venation. Studies on the diversity of A. longiloba focused mostly on morphological characteristics, while the genetic diversity of this species has never been published. This research aims to determine the genetic diversity and phylogeny of the Indonesian accession of A. longiloba based on molecular approaches using trnL-F IGS region. A total of 20 accesses of A. longiloba from Indonesia were sequenced then together with 11 DNA sequences of A. longiloba registered at the NCBI, were aligned with the Mesquite software. Genetic diversity was examined using DnaSP ver. 6.12.03. The phylogenetic tree was reconstructed by MEGA 11 using the Maximum Parsimony method and the Tree-Bisection-Regrafting (TBR) algorithm. Among 389 sites recorded, 356 site were invariable, 5 site were variable and 28 site were gaps or missing data. This genetic variation in the form of insertion, deletion, transition, and transversion and the deletion event has received the most contributions. Reconstruction of the phylogenetic tree resulted in A. longiloba being polyphyletic. The use of cpDNA with the trnL-F IGS region could not show the relationship between the Indonesian accession of A. longiloba, so further research is needed in other regions of chloroplast and nuclear DNA.